PENGARUH ETOS KERJA DAN RELIGIUSITAS TERHADAP KINERJA KARYAWAN BMT AL BAROKAH NGLUWAR SALAM MAGELANG - Muhammad Fatkhurohman Albashori; Subandi Subandi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to analyze employee performance in terms of work ethic and religiosity. This research is a quantitative research. This research method uses a questionnaire given to 70 employees of BMT Al Barokah Ngluwar Salam Magelang as a sample with purposive sampling technique. Measurement of variables using a Likert Scale. Data analysis using multiple regression analysis. The results of the analysis show that work ethic and religiosity affect employee performance.